Home-Based Physical Activity in Patients With Breast Cancer: During and/or After Chemotherapy? Impact on Cardiorespiratory Fitness. A 3-Arm Randomized Controlled Trial (APAC). (November 2020) - Vincent, François; Deluche, Elise; Bonis, Joëlle; Leobon, Sophie; Antonini, Marie-Thérèse; Laval, Caroline; Favard, Florent; Dobbels, Eloïse; Lavau-Denes, Sandrine; Labrunie, Anaïs; Thuillier, Frédéric; Venat, Laurence; et al.
Objectives: Physical activity (PA) programs are recommended for breast cancer care. However, their modalities remain to be discussed. This study determined the best time to begin a personalized or adapted program based on cardiopulmonary exercise test function. This randomized controlled trial evaluated the effect of home-based adapted PA (APA) performed during or after treatment on cardiorespiratory fitness (CRF) at 12 months. Method: The primary endpoint was the peak oxygen consumption (VO2peak ) at 12 months (group A vs C and B vs C). Secondary endpoints included the 6-minute walking test, assessment of muscle strength, fatigue, quality of life, anxiety, and depression, and a questionnaire on PA levels. All tests were evaluated at baseline and at 6 and 12 months. A total of 94 patients with breast cancer were randomized to 3 different groups: group A, performing 6 months of APA during adjuvant care; group B, 6 months of APA after adjuvant care; and group C, 12 months of APA during and after specific care. The program combined 1 resistance session and 2 aerobic sessions per week. Analysis of variance was used for repeated measures, Student's t -test or the Mann–Whitney U -test for continuous variables, and χ 2 test for binary or categorical variables. Results: The study assessed 81 participants at 6 months and 73 at 12 months. The majority of patients completed more than 85% of the exercise sessions. The baseline for VO2peak and secondary outcomes did not differ among the groups. VO2peak increased during the exercise period and decreased during the chemotherapy period without APA, but at 12 months no significant difference was observed. The same variation was observed in the 6-minute walking test, with significance at 6 months between A+C versus B ( P  = .04), but no difference among the groups at 12 months. In the 3 groups, no decreases in other studied parameters were noted, except at 6 months in group B without APA. Conclusion: Home-based APA in breast cancer patients has a positive effect on CRF and physical functions, with no differences based on the timing of this program based on specific cancer treatment. Trial Registration: ClinicalTrials.gouv.fr (NCT01795612). Registered 20 February 2013.